Maximising translational value of the Iowa gambling task in preclinical studies through the use of the rodent touchscreen - Judith A. Pratt; Brian J. Morris (Frontiers in Psychiatry)
The Iowa gambling task is widely employed to assess the evaluation of risk versus reward contingencies, and how the evaluations are implemented to gain advantageous returns. The cognitive processes involved can be compromised in psychiatric conditions, leading to the development of analogous tasks with translational value for use in rodents. The rodent touchscreen apparatus maximises the degree of similarity with the human task, and in this review we provide an outline of the use of rodent touchscreen gambling tasks in preclinical studies of psychiatric conditions. In particular, we describe how the basic task has been adapted to probe the relative contributions of different neurotransmitter systems, and specific aspects of cognition. We then offer a perspective on how the task might be employed most beneficially in future studies.